Hubungan Tingkat Pengetahuan dan Sikap Keluarga dengan Pencegahan Demam Berdarah Dengue di Wilayah Kerja Puskesmas Kedungmundu - Wildan Imaduddin; Moch Aspihan; Iskim Luthfa (Journal of Medical Practice and Research, 2025)
Background: Dengue Hemorrhagic Fever (DHF) is a public health threat in tropical regions such as Indonesia, with prevention highly dependent on family behavior. The level of knowledge and family attitudes are suspected to have a significant effect on the effectiveness of prevention efforts, but there are still gaps in their implementation, as seen in the work area of the Kedungmundu Health Center with quite high cases. The research method uses a cross-sectional design with a correlational quantitative approach. A sample of 66 families was selected using consecutive sampling techniques from a population of 205 dengue cases (March-May 2025). Data were collected through a structured questionnaire and analyzed univariate and bivariate using the Chi-Square test. Most respondents had a low level of knowledge (59.1%) and a negative attitude (68.2%) towards dengue prevention, with 62.1% indicating poor prevention practices. The results of the bivariate analysis showed that there was a significant relationship between the level of knowledge and the prevention of dengue (p=0.002; r=0.362) and between family attitudes and the prevention of dengue (p=0.000; r=0.632). The conclusion of this study There is a significant relationship between the level of knowledge and family attitudes and dengue prevention practices in the work area of the Kedungmundu Health Center, although the majority of respondents still have low knowledge, negative attitudes, and suboptimal prevention practices.